Copyright Enforcement: Evidence from Two Field Experiments. Issue 2 (30th September 2016) - Luo, Hong; Mortimer, Julie Holland
Abstract : Effective dispute resolution is important for reducing private and social costs. We study how resolution responds to changes in price and communication using a new, extensive data set of copyright infringement incidences by firms. The data cover two field experiments run by a large stock‐photography agency. We find that substantially reducing the requested amount generates a small increase in the settlement rate. However, for the same reduced request, a message informing infringers of the price reduction and acknowledging the possible unintentionality generates a large increase in the settlement rate; including a deadline further increases response rate. The small price effect, compared to the large message effect, can be explained by two countervailing effects of a lower price: an inducement to settle early, but a lower threat of escalation. Furthermore, acknowledging possible unintentionality may encourage settlement due to the typically inadvertent nature of these incidences. The resulting higher settlement rate prevents additional legal action and significantly reduces social costs.